Flexural Performance of a Novel Steel Cold-Formed Beam–PSSDB Slab Composite System Filled with Concrete Material - Mohammed Chyad Liejy; Ahmed W. Al Zand; Azrul A. Mutalib; Mustafa Farooq Alghaaeb; Ali A. Abdulhameed; Alyaa A. Al-Attar; Wadhah M. Tawfeeq; Salam J. Hilo (Buildings, 2023)
In this study, the flexural performance of a new composite beam–slab system filled with concrete material was investigated, where this system was mainly prepared from lightweight cold-formed steel sections of a beam and a deck slab for carrying heavy floor loads as another concept of a conventional composite system with a lower cost impact. For this purpose, seven samples of a profile steel sheet–dry board deck slab (PSSDB/PDS) carried by a steel cold-formed C-purlins beam (CB) were prepared and named “composite CBPDS specimen”, which were tested under a static bending load. Specifically, the effects of the profile steel sheet (PSS) direction (parallel or perpendicular to the span of the specimen) using different C-purlins configurations (double sections connected face-to-face, double separate sections, and a single section) were investigated. The research discussed the specimens’ failure modes, flexural behavior, bending capacity, bending strain relationships, and energy absorption index of specimens. Generally, the CBPDS specimens with the PSS slab placed in a parallel direction achieved approximately a 13–40% higher bending capacity compared with the corresponding specimens with a perpendicular PSS direction (depending on the configuration of the beam). Fabricating the beam of the CBPDS specimen with double C-purlins (face-to-face) led to more effective concrete confinement behavior compared with the double separate C-purlins beam. The related specimen recorded a 10% higher bending capacity. Finally, the suggested composite CBPDS system exhibited a sufficient energy absorption capability of the static bending load because it demonstrated high strength and high ductility.